Wheat seeding speed under no tillage (Revista de Ciências Agroveterinárias, 2008)
Several factors, such as operating speed, seeding depth, and soil moisture, can interfere with the implementation and establishment of crops during seeding, affecting their yield. This work aimed to assess the performance of two drillers, SDM 2023 from Metasa, with and without depth control wheels, and SHM 15 from Semeato, at different operating speeds. Seed distribution, seeding depth, percentage of soil surface covered with crop residues, wheat grain yield and yield components, were evaluated, using two experiments conducted on a typically dystrophic oxisol under no tillage. Wheat grain yield and yield components were not affected by treatments. The use of depth control wheels at the highest seeding speed (13.5 km h-1) increased the percentage of crop residues incorporated into the soil. High seeding speeds increased the operating capacity of drillers. However, it is important that the speeds are adequate for straw-cutting and furrowing operation to prevent wheat grain yield decrease.
Keywords: seeding speed; depth control wheels; depth.